O uso de aplicativo computacional como recurso pedagógico no ensino de solos nas séries iniciais do ensino fundamental de Pato Branco - PR - Camozzato, Silvana Tomazi (2015)
This study is the result of a qualitative research developed in the Graduate Program in Regional Development - PPGDR / 2014 on the use of computer application with soil content through a sample of groups of 4th year of elementary school in the municipal White-PR duck. We aimed to develop and evaluate the soil content drawn from diagnosis of prior knowledge of teachers and students using computer application as an educational resource. First the paper presents the theoretical framework with the objective of coordinating the different aspects that permeate the study of soil content. Following the work was divided into two chapters, where the first deals with the qualitative analysis of the textbook as opposed to some official documents. The second chapter corresponds to the development of lecture, practice, and evaluation of computer application use with soil content, given for Group Research and Popularization of Soil Science "Watch your step." To carry out the analysis, the methodology was based on questionnaires to teachers and students; the study textbook the 4th Year Science in contents for the soil and lecture with the strengthening of the computational application to students practical. As for the textbook, their analysis pointed out gaps, misconceptions and outdated concept. It also identified that the science textbook is the primary teaching tool for teachers to work with the soil content. It was found that for teachers lack expertise and complementary materials for the teaching soils. Regarding students, they had no information about the municipality's land. Both the lecture, and the practice of computer application resulted in completion and expansion of the soil content, specifically on municipal soil.